Sosialisasi Perilaku Hidup Bersih Dan Sehat Pasca COVID-19 - Silvia Nurvita; Siti Noor Chotimah; Viny Natalia Dewi; Ratih Kumala Dewi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2022)
Background: COVID-19 is an emerging infectious disease that is sweeping the world. Patients with COVID-19 in Indonesia have continued to increase since 2020. Prevention to break the transmission of COVID-19 includes carrying out complete vaccinations and applying clean and healthy living habits to each individual. After the COVID-19 pandemic, it is necessary to carry out outreach activities to the community regarding clean and healthy living behaviors to stop the transmission of COVID-19 and other infectious diseases. Method: community service uses a descriptive method, to describe ongoing socialization activities for clean and healthy living behavior after COVID-19. This activity was held on September 28 2022 in the Bugangan. Results: The socialization of clean and healthy living behavior (PHBS) in Bugangan was attended by the village head with a total of 19 participants consisting of RT/RW heads/deputies, health cadres. Participants had distributed leaflets PHBS before socialization. Evaluation of community service activities to assess participants' understanding in the form of asking questions. The presenter gave 3 questions related to PHBS to the participants present. The conclusion is that the community service activities are going well and can add to participants' understanding of PHBS in the family, especially the understanding of PHBS after COVID-19.